Effect of agrochemicals and irrigation regimes on productivity and profitability of barley (Hordeum vulgare L.) - Kavita; Amarjeet Nibhoria; Preetam Kumar (Annals of Agricultural Research, 2022)
The present study was conducted during Rabi, 2019-20 to evaluate the performance of various agrochemicals applied in barley under different irrigation levels. The investigation was carried out on six rowed dualpurpose BH-393 variety of barley at RRS, Bawal, CCSHAU, Hisar. The experiment was laid out in split plot design with three main plot and six sub plot treatments and replicated thrice. Main plot includes three water regimes viz. S0 -non stress (normal irrigation- irrigation at tillering and heading stage), S1 -moderate stress (irrigation withheld from tillering stage to season end) and S2 - severe stress (no irrigation); and subplot consists of six agrochemicals viz. control (T1 ), seed treatment with Tragacanth katira @ 100 g/kg seed (T2 ), soil application of Tragacanth katira @ 5 kg/ha(T3 ), foliar spray of salicylic acid @ 200 ppm at booting and grain formation stage (T4 ), combination of Tragacanth katira @ 2.5 kg/ha + foliar spray of salicylic acid @ 200 ppm at booting and grain formation stage (T5 ) and; foliar spray of KNO3 @ 1% at booting and grain formation stage (T6 ). Data revealed that highest grain yield and B: C ratio (5.0 t/ha, 2.06) was achieved under non stress and combination of Tragacanth katira with salicylic acid. Net returns were 31.3% and 35.8% higher in non stress and combination of Tragacanth katira with salicylic acid treatments as compared to their respective controls among water regimes and agrochemicals, respectively. The best treatment was a combination of Tragacanth katira with salicylic acid among agrochemicals and non stress in water regimes.